A kind of aminotriphenol rare earth catalyst and its preparation method and application
By using aminotriphenoloxycerium complex as a catalyst, the existing polylactic acid catalyst has been solved, and the high-efficiency synthesis of high molecular weight polylactic acid is achieved, which is suitable for the melt polymerization requirements of industrial production.
Patent Information
- Application Number
- CN202410695509.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-05-31
AI Technical Summary
The existing polylactic acid catalysts have small molecular weight, large catalyst usage during the synthesis process or do not meet the melt polymerization requirements of industrial production.
Using a rare earth catalyst of aminotriphenol, specifically an aminotriphenoloxycerium complex, is prepared by complexing reaction of aminotriphenol ligand and alkoxycerium metal salt under anhydrous and oxygen-free conditions, to catalyze the ring-opening polymerization of lactide.
High-efficiency catalytic ring-opening polymerization of lactide was achieved, and high molecular weight polylactic acid was prepared, with the highest number average molecular weight of up to 220,000, and it had high catalytic activity, fast polymerization speed and low toxicity.
Smart Images

Figure CN118754900B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth catalysts, and in particular relates to an aminotriphenol rare earth catalyst and a preparation method and application thereof. Background Art
[0002] Polylactic acid (PLA) is a biodegradable polymer. The monomer lactide used to synthesize polylactic acid has a wide range of biological sources, and the raw materials can be taken from crops such as corn and beets. In addition, polylactic acid materials have good biocompatibility, and pure chiral polylactic acid (such as PLLA) has good physical properties. Therefore, polylactic acid is currently one of the most promising materials to replace traditional petroleum-based plastics. The method for synthesizing polylactic acid in industry is through the ring-opening polymerization of lactic acid dimer lactide, mainly using stannous octoate as a catalyst. By adding alcohol to initiate the polymerization at a temperature above 180°C, high molecular weight polylactic acid can be obtained. However, stannous octoate has certain defects, such as low activity, poor selectivity, poor controllability, and certain biological toxicity. Therefore, the preparation of new catalysts is of great significance.
[0003] Chinese patent CN117229491A discloses a method for preparing polylactic acid using an organic base thiourea dual catalytic system. The system uses an organic base as a catalyst, is low in cost and does not contain metal elements, but the molecular weight of the polylactic acid obtained is less than 10 kDa, which is basically not worth processing; Chinese patent CN104892916A discloses a process for synthesizing biodegradable polylactic acid PLA by using an organic guanidine-non-toxic alcohol to catalyze the active bulk ring-opening polymerization of lactide LA. Under the conditions of 0.1 torr and 96-130° C., polylactic acid with a number average molecular weight of 10-50 kDa can be obtained, and the molecular weight is still relatively small; Chinese patent CN113527652A discloses a method for catalyzing the ring-opening polymerization of lactide using a Lewis acid-base pair, using one of low-toxic ferric chloride and dichloromethyl iron as a Lewis acid to form an acid-base pair with a Lewis base, adding alcohol as an initiator, and reacting at 180° C. to obtain a cyclic polylactic acid with a molecular weight of 13.6-119.6 kDa, but the amount of catalyst used is relatively large. In recent years, rare earth metals have given birth to unique rare earth metal organic chemistry due to their large ionic radius, high coordination number, strong Lewis acidity and other characteristics, and have developed many rare earth metal complexes with unique catalytic properties. The high coordination number of rare earth atoms makes them have strong coordination ability with monomers during the polymerization process, and they have high catalytic activity, fast polymerization speed and low toxicity. It is one of the hot research directions in polymer synthesis: Chinese patent CN09705328A provides phenol-oxazoline rare earth metal catalysts that can be directly used to catalyze cyclic esters such as ε-caprolactone, L-lactide, rac-lactide, meso-lactide, β-butyrolactone and carbonates. and the ring-opening polymerization of its derivatives; Chinese patent CN105037588B provides an isoindole rare earth metal catalyst that can catalyze the homopolymerization or copolymerization of olefins, alkynes, CO2, polar monomers such as oxirane or lactone, and can produce polylactic acid with a maximum number average molecular weight of 110kDa; Chinese patent CN104592425B provides a cycloheptatrienyl rare earth metal catalyst that can be applied to the polymerization of various monomers, including homopolymerization and copolymerization of olefins, alkynes, polar monomers, or copolymerization with CO2, respectively, to produce polylactic acid with a maximum number average molecular weight of 240kDa. However, the above rare earth catalysts catalyzed the ring-opening polymerization of lactide must be carried out in a solvent at room temperature, which does not meet the requirements of industrial production melt polymerization. Summary of the invention
[0004] The first purpose of the present invention is to solve the problem that the polylactic acid synthesized by the existing polylactic acid catalyst has a small molecular weight or a large catalyst dosage or does not meet industrial requirements, and to provide an aminotriphenol rare earth catalyst for synthesizing polylactic acid.
[0005] The second object of the present invention is to provide a method for preparing the above catalyst.
[0006] The third object of the present invention is to provide the use of the above catalyst.
[0007] The purpose of the present invention is specifically achieved through the following technical solutions:
[0008] An aminotriphenol rare earth catalyst, the structural feature of which is that the catalyst is an aminotriphenoloxycerium complex having the following general formula:
[0009]
[0010] In the general formula, R1 and R2 are each selected from one of hydrogen, tert-butyl, isopropyl, cumyl and adamantyl;
[0011] R is selected from one of C1-C4 alkyl, benzyl, aryl and methyl lactate.
[0012] The preparation method of the above-mentioned aminotriphenol rare earth catalyst, the aminotriphenoloxycerium complex is formed by the complexation reaction of aminotriphenol ligand and alkoxycerium metal salt in a solvent; the substituent of the aminotriphenol ligand is selected from one or two of hydrogen, tert-butyl, isopropyl, cumyl, and adamantane; the substituent of the alkoxycerium metal salt is selected from one of C1-C4 alkyl, benzyl, aryl, and methyl lactate.
[0013] Furthermore, the aminotriphenol ligand reacts with the alkoxy cerium metal salt under anhydrous and oxygen-free conditions.
[0014] Preferably, the solvent is selected from tetrahydrofuran (THF), toluene (Tol) and dichloromethane (DCM).
[0015] More preferably, the molar ratio of the aminotriphenol ligand to the alkoxycerium metal salt is 1:1.1-1.5, the reaction temperature is 0-40°C, and the reaction time is 3-27h.
[0016] Furthermore, the treatment method after the aminotriphenol ligand reacts with the alkoxycerium metal salt includes removing the solvent, recrystallizing, and vacuum drying.
[0017] Furthermore, the temperature for removing the solvent is 50° C.; the solvent used for the recrystallization is toluene and n-hexane.
[0018] The aminotriphenol rare earth catalyst is used for the ring-opening polymerization of lactone to obtain high molecular weight polyester.
[0019] Preferably, in the presence of alcohol, the lactone is polymerized at 0 to 180° C., and during the polymerization, the molar ratio of the catalyst to the alcohol to the lactone is 1:0 to 20:1 to 20000.
[0020] Further preferably, the lactone includes one of L-lactide, D-lactide, rac-lactide, meso-lactide, and brazilic acid ethylene glycol ester; the alcohol is a C1-C10 straight-chain, branched or cyclic alkyl alcohol, a C7-C20 single- or poly-aromatic substituted alkyl alcohol.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] The aminotriphenoloxy cerium complex of the present invention has extremely high activity in catalyzing the ring-opening polymerization of lactide and can be used for preparing high molecular weight polylactic acid, with the highest number average molecular weight reaching 220,000. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the lactide conversion rate of Example 5 1 H NMR spectrum;
[0024] Figure 2 It is the GPC curve diagram of the polylactic acid prepared in Example 5, the mobile phase is chloroform, and the measurement is carried out with PS as the standard. DETAILED DESCRIPTION
[0025] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0026] If the specific conditions are not specified in the examples of the present invention, the conventional conditions or the conditions recommended by the manufacturer are followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained by conventional technical means or purchased commercially. The GPC molecular weight in the implementation case is measured in THF relative to a narrow standard polystyrene (PS) standard, and the correction factor is 0.58.
[0027] Example 1
[0028] Preparation of tert-butylaminotriphenol catalyst ( tBu TPA-Ce):
[0029] a) Synthesis of cerium tert-butoxide: Under argon, sodium tert-butoxide (480 mg, 5 mmol) and ammonium cerium nitrate (663 mg, 1.21 mmol) were dissolved in dry tetrahydrofuran, and the sodium tert-butoxide solution was transferred to ammonium cerium nitrate. The mixture was reacted at room temperature for 3 h. The generated salt was filtered out using a sand core column, the solvent was drained, and the mixture was repeatedly extracted with n-hexane. The extract was concentrated and recrystallized to obtain 544 mg (78%) of a light yellow solid.
[0030] b) tert-butylaminotriphenol ligand (H3L tBu)Synthesis: Add 2,4-di-tert-butylphenol (16.5 g, 0.08 mol), formaldehyde solution (2.42 g), and hexamethylenetetramine (0.94 g, 0.0068 mol) into a 250 mL round-bottom flask, heat to 120°C and reflux for 72 h, cool to room temperature, add 100 mL of methanol and reflux for 1 h, cool to room temperature, filter to obtain a solid, and recrystallize with dichlorohexane to obtain a white solid, with a yield of 12.27 g (68.5%).
[0031] c) Synthesis of tert-butylaminotriphenol cerium ( tBu TPA-Ce: Under argon protection, tert-butylaminotriphenol (H3L tBu , 355.8 mg, 0.5 mmol) was dissolved in 10 mL of toluene, cerium tert-butoxide (344.9 mg, 0.6 mmol) was added, and the reaction was carried out at 25 ° C for 16 h, the solvent was dried at 50 ° C, and the product was recrystallized using n-hexane. The product was filtered onto a sand core plate and then vacuum dried at 40 ° C for 5 h to obtain a purple solid with a yield of 317.6 mg (72%).
[0032] Example 2
[0033] Preparation of adamantyl aminotriphenol catalyst ( AD TPA-Ce):
[0034] a) Adamantyl aminotriphenol ligand (H3L AD ) Synthesis: 4-tert-butylphenol (30.4g, about 200mmol), 1-adamantanol (30.6g, about 200mmol) and 11.1mL sulfuric acid were added to 400mL dichloromethane and reacted at room temperature for about 12h. The reaction mixture was washed with saturated sodium bicarbonate solution for several times and then separated with saturated brine and dichloromethane. The separated organic phase was dried with anhydrous sodium sulfate, filtered, and the solvent was drained. Column chromatography was used for separation and purification. The eluent was petroleum ether and ethyl acetate 10:1 to obtain 2-adamantanyl and 4-tert-butylphenol 33g (58%) as a white solid.
[0035] 2-adamantyl, 4-tert-butylphenol (11.7g, 41.2mmol), hexamethylenetetramine (0.84g, 6mmol), 4mL isopropanol and 0.4g p-toluenesulfonic acid were added to a 250mL round-bottom flask and heated to 140°C for six days. The reactant in the flask gradually turned bright yellow. After the reaction was completed, the temperature was restored to room temperature, 50mL of ethanol and 50mL of ether were added, and a white powder was obtained after stirring. The mixture was filtered, washed with ethanol, and the solvent was removed in vacuo to obtain 4.4g (32%) of white powder.
[0036] b) Synthesis of adamantyl aminotriphenol cerium catalyst ( ADTPA-Ce: In a glove box, adamantyl aminotriphenol ligand (H3L AD , 450.0 mg, 0.496 mmol) was dissolved in 10 mL of toluene, and cerium tert-butoxide (313.3 mg, 0.546 mmol) was added, and the reaction was carried out at 25°C for 20 h. The solvent was drained at 50°C, washed three times with n-hexane, and then recrystallized with toluene and n-hexane. The product was filtered onto a sand core plate, and then vacuum dried at 40°C for 5 h to obtain 360 mg (64%) of a purple solid.
[0037] Example 3
[0038] Preparation of cerium cumylaminotriphenol catalyst ( cum TPA-Ce):
[0039] a) Cumylaminotriphenol ligand (H3L cum ) Preparation:
[0040] i. 10.89 g (about 33 mmol) of 2,4-dicumylphenol, 1.1 g (about 7.8 mmol) of hexamethylenetetramine and 4 mL of glacial acetic acid were refluxed at 110° C. for 24 h. After 15 h of reaction, 0.3 g of hexamethylenetetramine (HMTA) was added and the reaction was continued for 9 h. The reaction was terminated when a large amount of methanol was immediately added when the mixture obtained by the reaction was not cooled and solidified. The obtained product was recrystallized three times with ether and methanol, filtered, and the solvent was removed under vacuum to obtain about 6.9 g (58%) of white powder.
[0041] 10 g of the white powder obtained above was refluxed with 20 mL of concentrated hydrochloric acid and 20 mL of ethylene glycol at 140° C. for three days, and the obtained mixture was directly filtered. The filtered solid was mixed with ethyl acetate and washed several times with a mixture of saturated sodium bicarbonate solution and saturated sodium chloride solution in a volume ratio of 1:20 until the solid was completely dissolved and there was no bubbling. After it was completely dissolved, it was washed three times with saturated sodium chloride solution, and then recrystallized three times with ether and methanol. The solvent was removed by vacuum stirring at 50° C. for 12 h to obtain a white powder (H2L cum )about 8.5g (86%).
[0042] ii. Stir 5.0 g of 2,4-dicumylphenol and 0.5 g of paraformaldehyde in 20 mL of acetic acid for 2 h to dissolve as much as possible. Then add 12 mL of 33% wt hydrogen bromide in acetic acid solution, react for 1 h, quench with ice water, and then separate with ethyl acetate and saturated brine 3 times, then add saturated sodium bicarbonate and wash quickly several times until there is no acetic acid smell to remove excess acetic acid, spin dry and recrystallize twice with ether and methanol, use column chromatography, use ethyl acetate and n-hexane as eluents to separate and obtain a white powder product 2,4-dicumyl, 6-bromomethylphenol about 3.8 g (59%).
[0043] iii. 780 mg of H2L cum The mixture was refluxed in 10 mL of tetrahydrofuran solution with 480 mg of 2,4-dicumyl, 6-bromomethylphenol and 150 μL of triethylamine for 5 h, and then filtered to remove the generated triethylamine salt. The filtrate was spin-dried and recrystallized three times with ether and ice methanol, and then recrystallized twice with methanol by heating and cooling. The solvent was removed by vacuum stirring at 70° C. overnight, and a white powder product (H3L) was obtained by column chromatography with ethyl acetate and n-hexane as eluents. cum ) about 580 mg (52%).
[0044] b) Preparation of cerium cumylaminotriphenolate ( cum TPA-Ce):
[0045] Synthesis of cerium cumylaminotriphenol: Under argon protection, cumylaminotriphenol (H3L cum , 522 mg, 0.5 mmol) was dissolved in 10 mL of toluene, tert-butoxide cerium (344.87 mg, 0.6 mmol) was added, and the reaction was carried out at 25°C for 20 h. The solvent was dried at 50°C, and the product was recrystallized using n-hexane. The product was filtered onto a sand core plate and then vacuum dried at 40°C for 5 h to obtain a purple solid with a yield of 471 mg (71%).
[0046] Example 4
[0047] Under argon conditions, 180 mg L-LA (L-lactide) and 1.1 mg tert-butylaminotriphenol cerium were added to a catalyst bottle equipped with a magnetic stirrer, wherein [LA]:[ tBu TPA-Ce] = 1000:1 (molar ratio of substances), react at 140°C for 10 min. Cool to room temperature, dissolve in dichloromethane, add n-hexane to precipitate the polymer, and dry in vacuum. Conversion rate 94%, M n,GPC =14.7×10 4 g / mol, molecular weight distribution PDI=1.27.
[0048] Example 5
[0049] Under argon conditions, add 480 mg L-LA, 1.1 mg tert-butylaminotriphenol cerium, and 200 μL toluene to a catalyst bottle equipped with a magnetic stirrer. tBu TPA-Ce] = 3000:1 (molar ratio of substances), react at 140°C for 20 min. Cool to room temperature, dissolve in dichloromethane, add n-hexane to precipitate the polymer, and dry in vacuum. Conversion rate 97%, M n,GPC =22.44×10 4g / mol, molecular weight distribution PDI=1.35.
[0050] Example 6
[0051] Under argon conditions, add 1.60g L-LA, 1.0mg tert-butylaminotriphenol cerium, 0.0114mmol benzyl alcohol (114mg benzyl alcohol toluene solution with a concentration of 0.1mmol / g), and 200μL toluene to a catalyst bottle equipped with a magnetic stirrer. tBu TPA-Ce] = 10000:10:1 (molar ratio of substances), react at 140°C for 50 min. Cool to room temperature, dissolve in dichloromethane, add n-hexane to precipitate the polymer, and dry in vacuum. Conversion rate 84%, M n,GPC =9.98×10 4 g / mol, molecular weight distribution PDI=1.38.
[0052] Example 7
[0053] Under argon conditions, add 3.20g L-LA, 1.0mg tert-butylaminotriphenol cerium, 0.0114mmol benzyl alcohol (114mg benzyl alcohol toluene solution with a concentration of 0.1mmol / g), and 200μL toluene to a catalyst bottle equipped with a magnetic stirrer. tBu TPA-Ce] = 20000:10:1 (molar ratio of substances), react at 140°C for 70 min. Cool to room temperature, dissolve in dichloromethane, add n-hexane to precipitate the polymer, and dry in vacuum. Conversion rate 62%, M n,GPC =10.09×10 4 g / mol, molecular weight distribution PDI=1.36.
[0054] Example 8
[0055] Under argon conditions, add 1.60g L-LA, 1.0mg tert-butylaminotriphenol cerium, 0.0114mmol benzyl alcohol (114mg benzyl alcohol toluene solution with a concentration of 0.1mmol / g), and 200μL toluene to a catalyst bottle equipped with a magnetic stirrer. tBu TPA-Ce] = 10000:10:1 (molar ratio of substances), react at 170°C for 50 min. Cool to room temperature, dissolve in dichloromethane, add n-hexane to precipitate the polymer, and dry in vacuum. Conversion rate 95%, M n,GPC =11.74×10 4 g / mol, molecular weight distribution PDI=1.54.
[0056] Example 9
[0057] In a glove box, 934 mg of tert-butylaminotriphenol was dissolved in 20 mL of toluene, and then 877 mg of tert-butyl cerium was added and stirred at room temperature for 16 h. 2 kg of industrial lactide was added to the reactor, and nitrogen was replaced three times. The reaction solution was taken out of the glove box and directly poured into the reactor. The metal loading was 109 ppm, [LA]:[tBUOH]:[ tBu TPA-Ce] = 10000:3:1, 150℃ for 1h, then heated to 170℃ for 5h, and then discharged directly. Conversion rate 85%, Mn ,GPC =10.17×10 4 g / mol, molecular weight distribution PDI = 1.74. (GPC molecular weight is measured in dichloromethane mobile phase, with PS as standard.)
[0058] Example 10
[0059] Under argon conditions, 144 mg L-LA and 1.1 mg adamantane aminotriphenol cerium were added to a catalyst bottle equipped with a magnetic stirrer. AD TPA-Ce] = 1000:0:1 (molar ratio of substances), react at 170°C for 10 min. Cool to room temperature, dissolve in dichloromethane, add n-hexane to precipitate the polymer, and dry in vacuum. Conversion rate 93%, M n,GPC =10.79×10 4 g / mol, molecular weight distribution PDI=1.37.
[0060] Embodiment 11
[0061] Under argon conditions, add 1.44g L-LA, 1.1mg adamantane aminotriphenol cerium, 0.01mmol benzyl alcohol (100mg benzyl alcohol toluene solution with a concentration of 0.1mmol / g), and 200μL toluene to a catalyst bottle equipped with a magnetic stirrer. AD TPA-Ce] = 10000:10:1 (molar ratio of substances), react at 170°C for 2h. Cool to room temperature, dissolve in dichloromethane, add n-hexane to precipitate the polymer, and dry in vacuum. Conversion rate 82%, M n,GPC =5.37×10 4 g / mol, molecular weight distribution PDI=1.56.
[0062] Example 12
[0063] Under argon conditions, add 1.44g L-LA, 1.1mg cumyl aminotriphenol cerium, 0.01mmol benzyl alcohol (100mg benzyl alcohol toluene solution with a concentration of 0.1mmol / g), and 200μL toluene to a catalyst bottle equipped with a magnetic stirrer. cum TPA-Ce] = 10000:10:1 (molar ratio of substances), react at 170°C for 2h. Cool to room temperature, dissolve in dichloromethane, add n-hexane to precipitate the polymer, and dry in vacuum. Conversion rate 80%, M n,GPC =5.22×10 4 g / mol, molecular weight distribution PDI=1.40.
[0064] The following table shows the experimental data of Examples 4-12
[0065]
[0066] The initiator was BnOH, the GPC molecular weight was determined in THF relative to a narrow PS standard, and the correction factor was 0.58.
[0067] * The initiator described in Example 9 is tert-butyl alcohol generated by the in-situ reaction of triphenol ligand and cerium tert-butyl alcohol instead of external benzyl alcohol. The GPC results of the prepared polylactic acid are measured in chloroform mobile phase relative to PS as standard.
[0068] It can be seen from the experimental data that the aminotriphenoloxycerium complex in the example has extremely high activity in catalyzing the ring-opening polymerization of lactide, and the maximum number average molecular weight of the synthesized polylactic acid can reach 224.4 KDa.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An aminotriphenol rare earth catalyst, characterized in that: The catalyst is an aminotriphenoloxycerium complex having the following general formula: In the general formula, R1 and R2 are each selected from tert-butyl, isopropyl, cumyl, and adamantyl; R is selected from C1-C4 alkyl.
2. The method for preparing the aminotriphenol rare earth catalyst according to claim 1, characterized in that: The aminotriphenoloxycerium complex is formed by complexation reaction between an aminotriphenol ligand and an alkoxy cerium metal salt in a solvent; the substituent of the aminotriphenol ligand is selected from one or two of tert-butyl, isopropyl, cumyl and adamantane; and the alkoxy cerium metal salt is tert-butyl cerium.
3. The method for preparing the aminotriphenol rare earth catalyst according to claim 2, characterized in that: The aminotriphenol ligand reacts with the alkoxy cerium metal salt under anhydrous and oxygen-free conditions.
4. The method for preparing the aminotriphenol rare earth catalyst according to claim 3, characterized in that: The solvent is selected from tetrahydrofuran, toluene and dichloromethane.
5. The method for preparing the aminotriphenol rare earth catalyst according to claim 4, characterized in that: The molar ratio of the aminotriphenol ligand to the alkoxy cerium metal salt is 1:1.1-1.5, the reaction temperature is 0-40°C, and the reaction time is 3-27h.
6. The method for preparing the aminotriphenol rare earth catalyst according to claim 2, characterized in that: The treatment method after the aminotriphenol ligand reacts with the alkoxy cerium metal salt includes removing the solvent, recrystallizing, and vacuum drying.
7. The method for preparing the aminotriphenol rare earth catalyst according to claim 6, characterized in that: The temperature for removing the solvent is 50° C.; the solvents used for the recrystallization are toluene and n-hexane.
8. The use of the aminotriphenol rare earth catalyst according to claim 1, characterized in that: The aminotriphenol rare earth catalyst is used for the ring-opening polymerization of lactone to obtain high molecular weight polyester, and the lactone is L-lactide.
9. The use according to claim 8, characterized in that: In the presence of alcohol, the lactone is polymerized at 0-180°C, and the molar ratio of the catalyst to the alcohol and the lactone during the polymerization is 1:0-20:1-20000.
10. The use according to claim 9, characterized in that: The alcohol is a C1-C10 straight-chain, branched or cyclic alkyl alcohol, or a C7-C20 single- or multi-aryl-substituted alkyl alcohol.
Citation Information
Patent Citations
A cycloheptatrienyl rare earth metal catalyst, preparation method and application
CN104592425B
Technology for controlled synthesis of polylactic acid through lactide activity ring-opening polymerization under catalytic action of organic guanidine-nontoxic alcohol
CN104892916A
An isoindole rare earth metal catalyst, its preparation method and application
CN105037588B
Method for catalyzing ring-opening polymerization of lactide by using Lewis acid-base pair
CN113527652A
Method for preparing polylactic acid by using organic alkali thiourea dual-catalysis system
CN117229491A